Research on the Power Matching Method of Dual-motor Driven Centrifuge - Chen , Yongwen; Hou, Yongjun; Mou, Changqing; Lian, Zhe; Ma, Yongheng (Scientific Journal of Technology, 2026)
To address the power loss and high-frequency "material jamming" issues caused by improper motor selection in dual-motor driven horizontal screw discharge centrifuges, this paper proposes a motor power calculation method based on a 2K-H differential transmission mechanism to optimize motor configuration. First, the rotational speed relationships between the components of the differential are systematically analyzed using the transmission ratio method, and the external torque distribution of each component is derived using the torque balance equation, laying a theoretical foundation for power distribution. Second, taking the LW450 centrifuge as the research object, the power variation laws of the main and auxiliary motors under different drum speeds and differential conditions are explored in depth. The changing trends of the torque of the main shaft and differential input shaft with the drum speed are revealed, and the calculation results are matched with the actual pushing torque requirements to determine the optimized power configuration scheme for the main and auxiliary motors. Subsequently, electromechanical co-simulation is performed using Simulink-Recurdyn to reproduce the differential collapse phenomenon caused by insufficient braking capacity of the auxiliary motor, and it is verified that the slag production can be increased by approximately 1.8 times. Finally, a finite element analysis was conducted to investigate the impact of optimization on the centrifuge structure. The results showed that the optimized auxiliary motor's power torque can maintain balance with the frictional torque under high load, thereby reducing stress by approximately 89%. This dual-motor power matching method is also applicable to other centrifuge models, further improving the overall performance and operational stability of the centrifuge.